The Yale guide to children's nutrition - Tamborlane, William V.; Weiswasser, Janet Z. (Yale University Press, 1997)
What is the healthiest diet for an infant? What constitutes a nutritious school lunch? How do I deal with my adolescent's eating needs and habits? Will my children receive proper nutrients if they are sick, very athletic, or vegetarians? This authoritative resource answers these and dozens of other questions, not only presenting the latest scientific knowledge about nutrition but also providing recipes from famous chefs for delicious and healthy dishes. The book, written by physicians and dietitians at the Yale University School of Medicine, an international leader in pediatric teaching, research, and clinical care, as well as by dietitians, nurses, and social workers at the Yale-New Haven Children's Hospital, is the most authoritative, comprehensive, and informative guide to childhood nutrition ever produced.